PENINGKATAN KESIAPAN PERSALINAN MELALUI EDUKASI MANDIRI BAGI IBU HAMIL TRIMESTER KETIGA DI PMB SHINTA KOTA MEDAN PROVINSI SUMATERA UTARA TAHUN 2025: PENINGKATAN KESIAPAN PERSALINAN MELALUI EDUKASI MANDIRI BAGI IBU HAMIL TRIMESTER KETIGA DI PMB SHINTA KOTA MEDAN PROVINSI SUMATERA UTARA TAHUN 2025 - Marta Armita Silaban; Yasrida Nadeak; Novita Andriani Br.Manjorang; Damayanty S; Eva Dona Sinaga (Bengkulu Institute, 2025)
Preparing for childbirth is one of the most important strategies to reduce the risk of complications for both mother and baby. However, many pregnant women, especially those in their third trimester, do not fully understand the signs of labor, how to deliver a baby, and how to prepare for referrals. Pregnant women about to give birth often experience anxiety due to their inability to cope with the discomfort caused by the mental and physical changes that occur during pregnancy. This community service program aims to improve the readiness of pregnant women in their third trimester for childbirth through independent learning based on educational e-books. This community service activity took place at PMB Shinta, Medan Johor District, Medan City, involving thirty-two expectant mothers. Activities included small group discussions, counseling, distribution of e-books, and prenatal and postnatal examinations for evaluation. The results of this community service program indicated that participants now have a better understanding and are prepared for the labor process. Pregnant women can gain the basic knowledge needed before giving birth through this e-book. The goal of this community service initiative is to improve the readiness of pregnant women in their third trimester for childbirth through independent learning based on educational e-books.